Writing Literature Review: Perceptions of Science Education Final Year Undergraduate Students in Tertiary Institutions in Gombe State - Dogo , Peter; Ayuba, Bala; Biwai, Yahuza; Ibrahim, Luther (Kashere Journal of Education, 2025)
The study investigated the writing literature review: perception of science education final year undergraduate students in tertiary institutions in Gombe State, Nigeria The study employed a descriptive survey research design. The target population for the study was 1020 final-year students from the study institutions. The sample of 287 respondents was retained using the Yamane method. A purposeful sampling technique was also employed for choosing the category of subjects. The study used a questionnaire instrument to seek responses from respondents based on research questions designed for the study. Findings revealed few (25.0%) candidates do perceive a conceptual framework in literature writing. More (89%) of the same candidates did not agree with the perceived theoretical framework in a literature writing, while few (15.0%) strongly agreed with the perceived empirical review study as an aspect of a literature writing. Further findings revealed 30% of candidates perceived gap identification as a requirement in chapter summary in literature review writing. The implication here is that there is a very low level of perception of literature review writing among undergraduate final-year students in science education. The study recommended that students should be taught literature review writing in their research methodology. The need to engage final-year candidates on concept paper presentations during lectures seminar and workshops.